Definition, elements and stages of elaboration of research protocols (Research, Society and Development, 2020)
Although it is recognized as an instrument capable of guaranteeing transparency and assertiveness in scientific investigations, the research protocol is still little known by the academic community. The present study addresses research protocols with focus on three aspects: what they are, what characterizes them and how they are developed. The method used was the conceptual bibliography, based on the scientific papers available in the Google Scholar and Science Direct databases. The definitions found in the scientific literature consulted were interpreted based on techniques of semantic and content analysis. The results showed that: a) the research protocol is the outline of the methodology for collecting and analyzing data in order to achieve the research objectives, b) the protocols are composed of four stages: introductory, procedural, practical and drafting and c) the steps follow a procedural logic, in which the introductory excerpt describes the theme of the study, the procedural phase details the strategies used to collect and analyze data, the practical phase consists of obtaining the data that will support the research analysis and the editorial part it concerns the preparation of manuscripts for publication. The conclusion shows that the research protocols are methodological instruments used to guarantee the validity and reliability of the results.